Six-month Outcomes and Predictors Following Non-ST Elevation Myocardial Infarction Managed by Internists - Daniel, Jaifrin; Hansdak, Samuel George; Iyadurai, Ramya; Ralph, Ravikar; Gunasekaran, Karthik; Miraclin, T Angel; Jayaseelan, Visalakshi; Sudarsanam, Thambu David (CHRISMED Journal of Health and Research, 2023)
Background: Acute coronary syndrome (ACS) is associated with significant morbidity and mortality. There is an increase in the proportion of non-ST elevation myocardial infarction/unstable angina (NSTEMI/UA) but there is a sparsity of data about the long-term outcome of patients with NSTEMI managed by internists. The long-term outcome and predictors of mortality of individuals with NSTEMI, managed by internists were the subject of the present study. Methods: This is a prospective observational cohort study of patients admitted under the internal medicine units with ACS. One hundred forty participants were recruited from April 2016 to July 2017. The various clinical outcomes and all-cause mortality at discharge, 1 month and 6 months were recorded. Results: During the study, 132 patients had NTSEMI/UA while 8 had ST-elevation myocardial infarction; 53.2% were men. The mean age was 63.6 ± 11.8 years for NSTEMI/UA. The mean duration of onset of symptoms to primary care was 29.14 ± 34.6 h; 39 (27.9%) presented beyond 48 h. The most frequent comorbidities observed were diabetes mellitus 96 (68.6%), hypertension 94 (67.1%), and dyslipidemia 44 (31.4%). Fifty-two (37.1%) required respiratory support. All patients received Antiplatelet agents and statins. Mortality rates were 9.1%, 13.4%, and 16.1% at discharge, 1-month, and 6 month following admission. The median survival was 161 (147-175) days. Dyslipidemia (hazard ratio [HR]: 0.55, 95% confidence interval [CI]: 0.26, 1.15, P = 0.110) and smoking (HR: 2.16, 95% CI: 1.16-4.02, P = 0.015) were identified as risk factors which predicted mortality. Conclusions: Mortality rates following NSTEMI, managed by internists at our tertiary care hospital was similar to various national and international registries. Smoking and dyslipidemia were predictors of mortality.